Antioxidant Activity of Selenium Containing Analogues: A Review of Glutathione Peroxidase and Antioxidant Mechanism - Lamani, Devappa S.; Lamani, Shekappa D. (Chemistry and Biochemistry: Research Progress Vol. 3, 2025)
This chapter provides information published in recent years on the chemical forms, particularly on the antioxidant and prooxidant activities of organoselenium compounds. In the present study, a series of functional mimics of synthetic antioxidant organoselenium compounds such as ebselen, Allyl selenides, selenenate esters, Diferrocenyldiselenides, spirodioxyselenurane, spirodiazaselenuranes and its glutathione peroxidase (GPx) catalytic activity are discussed. The first synthetic compound ebselen and its related compounds show significant antioxidant activity. Therefore, initial successes of ebselen exhibited beneficial effects in clinical trials. Further, diferrocenyldiselenides containing tert-amino substituents exhibited excellent GPx activity in the presence of PhSH and imported remarkably higher activity than that of ebselen. In addition, spirodioxyselenurane and spirodiazaselenuranes are structurally interesting compounds and the stability of these compounds highly depends on the nature of the substituents attached to the nitrogen atom. The high concentration of peroxides addition the selenium centre in the spirocyclic compounds undergoes further oxidation to produce the corresponding selenurane oxides, which are stable at room temperature. The overall use of synthetic reagents is becoming increasingly popular for pre-clinical studies and bio-medicinal applications.